Pharmacokinetic evaluation and bioavailability of KPT-335 (Verdinexor) in cats - Yang, Yuxin; Meng, Jinyan; Wen, Zeyu; Wang, Jianzhong; Cao, Xingyuan (Frontiers in Veterinary Science, 2025)
KPT-335 (Verdinexor) is a novel, orally bioavailable selective inhibitor of nuclear export that has gained significant attention in pharmaceutical research due to its potential anti-tumor and antiviral effects. This study aimed to evaluate the pharmacokinetic parameters and determine the absolute bioavailability of KPT-335 through various administration routes, including oral capsules and tablets, along with intravenous injections. The intravenous group received a dosage of 1 mg/kg body weight (BW), while capsules were administered orally at doses of 0.2, 1, and 2 mg/kg BW. Tablets were also administered orally at 1 and 2 mg/kg BW, with both post-feeding and fasting conditions at the 1 mg/kg BW dosage. Plasma concentrations of KPT-335 were analyzed using ultra-performance liquid chromatography/tandem mass spectrometry. Key pharmacokinetic parameters, including peak concentration (Cmax), area under the curve (AUC0–last), and terminal phase elimination half-life (T1/2), were determined through non-compartmental analysis using WinNonlin 8.1. The absolute bioavailability rates of 43.72, 44.66, and 28.92% for the low, medium, and high-dose capsule groups, respectively. In the tablet formulation, bioavailability at 1 mg/kg BW (fasting), 1 mg/kg BW (feeding), and 2 mg/kg BW (feeding) were 75.92, 70.98, and 47.27%, respectively. KPT-335 demonstrated pharmacokinetic characteristics of rapid absorption and elimination. The results demonstrated that KPT-335 exhibited non-linear pharmacokinetic behavior, indicating that higher doses are not fully absorbed in cats. This finding provides data support for guiding clinical dosing regimens. At the same dose, the absolute bioavailability of the tablet group was higher than that of the capsule group.